Resistance to BTK inhibition by ibrutinib can be overcome by preventing FOXO3a nuclear export and PI3K/AKT activation in B-cell lymphoid malignancies - Kapoor, Isha (Cell Death Dis, 2019)
Chronic activation of the Bruton’s tyrosine kinase (BTK)-mediated B-cell receptor (BCR) signaling is a hallmark of many B-cell lymphoid malignancies, including chronic lymphocytic leukemia (CLL) and diffuse large B-cell lymphoma (DLBCL). Ibrutinib, an FDA approved, orally administered BTK inhibitor, has demonstrated high response rates, however, complete responses are infrequent and acquired resistance to BTK inhibition can emerge. In this study, we generated ibrutinib-resistant (IB-R) cell lines by chronic exposure of CLL and activated B-cell (ABC)-DLBCL cells to ibrutinib in order to investigate the mechanism of acquired resistance to ibrutinib. IB-R cell lines demonstrated downregulation of FOXO3a and PTEN levels and activation of AKT, with their levels being low in the nuclei of resistant cells in comparison to the sensitive counterparts. Inhibition of PI3K and AKT using idelalisib and MK2206, respectively increased ibrutinib-induced apoptosis in IB-R cells by downregulation of pAKT(473) and restoring FOXO3a levels, demonstrating the importance of these cell survival factors for ibrutinib-resistance. Notably, the exportin 1 inhibitor, selinexor synergized with ibrutinib in IB-R cells and restored nuclear abundance of FOXO3a and PTEN, suggesting that nuclear accumulation of FOXO3a and PTEN facilitates increase in ibrutinib-induced apoptosis in IB-R cells. These data demonstrate that reactivation of FOXO3a nuclear function enhances the efficacy of ibrutinib and overcomes acquired resistance to ibrutinib. Together, these findings reveal a novel mechanism that confers ibrutinib resistance via aberrant nuclear/cytoplasmic subcellular localization of FOXO3a and could be exploited by rational therapeutic combination regimens for effectively treating lymphoid malignancies.